The study of human genome collaborating for comprehension, diagnosis and prevention of genetic diseases; the example of neuromuscular diseases - Zatz, Mayana (Revista de Medicina, 2001)
The announcement of the finishing of the Human Genome will start to bring many responses related to the molecular aspect of diverse diseases but also it will bring many questions as: Which is the benefit for the Medicine in studying the genes? Which is the involved ethical aspects? Which are the real perspectives ahead of this discovery? To study genetic illnesses assists the study of the genes even though in its ethical aspect, exactly in view of that the Human Genome has brought little of new developments for the main genetic illnesses, since its genes already were known. Here the example of the Neuromusculares Illnesses will be shown, more accurately the Muscular Dystrophies, since its genetic and molecular aspects until its different presentations, its diagnosis, the factors of risk and the involved questions in the genetic counseling.